Vacuum-plasma properties of stainless steel after impact of combined glow-microwave discharges in argon atmosphere - Glazunov, G.P.; Moiseenko, V.E.; Maznichenko, S.M.; Bondarenko, M.N.; Konotopskiy, A.L.; Tarasov, I.K.; Shapoval, A.N. (Вопросы атомной науки и техники, 2021)
The experiments were carried out to determine the vacuum-plasma characteristics (mainly erosion and outgassing rate in a vacuum) of the stainless steel 12X18H10T before and after processing the walls of the vacuum chamber with the glow discharge and combined, glow-microwave plasma discharges in argon atmosphere. The current-voltage characteristics, the electron density and electron temperature were measured. It was observed that the discharge voltage in the combined regime is significantly lower than in glow discharges. In some modes, this voltage decrease can be up to 200 V. It was shown that erosion of stainless steel 12X18H10T in the combined discharges is ≈ 70 %, less than in the glow discharges. Measurements were made of the outgassing rate of 12X18H10T stainless steel with the thermal desorption probe in situ in the DSM-1 vacuum chamber. It was shown that cleaning the chamber wall by the glow discharge during 5 h leads to a decrease in the outgassing rate from 5.5·10⁻⁵ to 1·10⁻⁵ (Torr.l)/(s.cm²). When the chamber wall is treated with GM discharge starting from nearly the same initial conditions the outgassing rate decreased to 3·10⁻⁶ (Torr.l)/(s.cm²). Spectral measurements of the plasma radiation of a glow and combined discharges show a decrease in the ratio of the peaks of argon ions and neutrals during the transition from a glow discharge to a combined one. Проведені експерименти з визначення вакуумно-плазмових характеристик (ерозія, газовиділення у вакуумі) нержавіючої сталі 12Х18Н10Т до і після обробки стінок вакуумної камери плазмою тліючого і комбінованого (тліючий розряд з введенням НВЧ-потужності) розрядів в аргоні. Вимірювались вольтамперні характеристики, електронна густина, потенціал плазми. Показано, що напруга розряду в комбінованому режимі істотно нижча, ніж у тліючому. У деяких режимах це зниження може бути до 200 В. Показано, що ерозія нержавіючої сталі 12Х18Н10Т у комбінованому розряді приблизно на 70 % менша, ніж у тліючому. Проведені вимірювання швидкості газовиділення нержавіючої сталі 12Х18Н10Т in situ у вакуумній камері ДСМ-1. Показано, що чищення стінки камери тліючим розрядом протягом 5 годин призводить до зниження швидкості газовиділення з 5,5·10⁻⁵ до 1·10⁻⁵ (Торр·л)/(с·см²). А при обробці стінки камери комбінованим розрядом за цей же час швидкість газовиділення зменшується до 3·10⁻⁶ (Торр·л)/(с·см²). Проведені спектральні вимірювання випромінювання плазми тліючого і комбінованого розрядів. Аналіз спектрів показує зменшення співвідношення інтенсивностей піків іонів аргону і нейтралів при переході від тліючого розряду до комбінованого. Проведены эксперименты по определению вакуумно-плазменных характеристик (эрозия, газовыделение в вакууме) нержавеющей стали 12Х18Н10Т до и после обработки стенок вакуумной камеры плазмой тлеющего и комбинированного (тлеющий разряд с введением СВЧ-мощности) разрядов в аргоне. Измерены вольт-амперные характеристики, электронная плотность, потенциал плазмы. Показано, что напряжение разряда в комбинированном режиме существенно ниже, чем в тлеющем. В некоторых режимах это снижение может быть до 200 В. Показано, что эрозия нержавеющей стали 12Х18Н10Т в комбинированном разряде на ≈ 70 % меньше, чем в тлеющем. Проведены измерения скорости газовыделения нержавеющей стали 12Х18Н10Т in situ в вакуумной камере ДСМ-1. Показано, что чистка стенки камеры тлеющим разрядом в течение 5ч приводит к снижению скорости газовыделения примерно в пять раз ‒ с 5,5·10⁻⁵ до 1·10⁻⁵ (Торр·л)/(с·см²). А при обработке стенки камеры комбинированным разрядом за это же время скорость газовыделения снижается до 3·10⁻⁶ (Торр.л)/(с.см²). Проведены спектральные измерения излучения плазмы тлеющего и комбинированного разрядов. Анализ спектров показывает уменьшение соотношения интенсивностей пиков ионов аргона и нейтралов при переходе от тлеющего разряда к комбинированному.